The development and optimization of an innovative piezoelectric energy harvester on the basis of vapor-induced vibrations. (15th September 2019) - Hsieh, Jui-Ching; Lin, David T.W.; Lin, Chia-Li
Highlights: Optimization for harvester based on the vibration induced by vapor flow. The vapor flows over the harvester resulted in 60 Hz of periodicity vibration. GA method used to optimize harvester dimensions for achieving 60 Hz. The optimized and simulated results were verified by experiment. Maximum output power occurred at resonance of vortex vibration and harvester. Abstract: Various energy harvesters were developed by several energy sources. In the heat pipe, the vapor momentum can be used to drive a mechanical structure to generate electricity. To bridge this gap, this study experimentally designed an energy harvester on the basis of a vapor-induced vibration for the innovative heat pipe application. The energy harvester, comprising a cantilever beam and polyvinylidene fluoride (PVDF), was designed using finite element method and the genetic algorithm (GA) to reach the resonance point. Copper, aluminum, and polyethylene (PE) were used as the material of the cantilever beam for the energy harvester. The optimized energy harvester was examined using a shocker, and obtained the output voltage. The output power of the harvester was affected by the vapor velocity, cantilever beam material, and natural frequency. The output voltages of the PVDF with the cantilever beam are better than the one of PVDF without the cantilever beam and it increased 367%, 393%, and 470%ascantilever beam is copper, aluminum, and polyethylene, respectively. The theoretical and practical implication, limitations of the present study for future studies are presented and studied.